Lipid Metabolism in Regulation of Macrophage Functions. Issue 12 (December 2020) - Yan, Jiawei; Horng, Tiffany
Abstract : Macrophages are cells of the innate immune system that regulate the maintenance of tissue homeostasis, host defense during pathogen infection, and tissue repair in response to tissue injury. Recent studies indicate that macrophage functions are influenced by cellular metabolism, including lipid metabolism. Here, we review how macrophage lipid metabolism can be dynamically altered in different physiological and pathophysiological contexts and the key regulators involved. We also describe how alterations in lipid metabolism are integrated with the signaling pathways that specify macrophage functions, allowing for coordinated control of macrophage biology. Finally, we discuss how dysregulated lipid metabolism contributes to perturbed macrophage functions in settings such as atherosclerosis and pathogen infections. Highlights: Macrophages have diverse roles depending on the setting. They maintain tissue homeostasis at steady state, and can be activated to assume new, context-dependent functions in response to infection, metabolic stress, and tissue damage. Lipid metabolism has a key role in regulating macrophage functions. Signals that drive macrophage activation (e.g., to an inflammatory state that regulates host defense) impinge on metabolic-sensing pathways to coordinate shifts in lipid metabolism. Lipids are a source of energy for macrophages, and provide precursors for bioactive lipids and components of cellular membranes. Lipids also regulate signal transduction and gene regulation during macrophage activation. Dysregulated lipid metabolism is implicated in aberrant macrophage functions, for example, in atherosclerosis and obesity or in certain intracellular infections.